Mergers and Acquisitions: A Comparative Review Of Literature - Ghosh, Sohini; Dutta, Sraboni (Industrija, 2016)
The paper aims to review scholastic research on the effect of M&As on firm performance and present a comparative analysis of Indian M&As vis-a-vis those occurring in other nations. 108 articles in referred journals published between 2005 and 2015 have been surveyed with a focus on comparing firm performance parameters prior and post the M&A. Firm performance has been inspected via three measures i.e.  accounting measures, stock market performance measures and qualitative measures. On the basis of these three measures, literature on mergers in India with those occurring in another 23 countries was compared. The review has shown that irrespective of the nation, M&As may impact the accounting and stock market performance measures of the acquirer and target firms in a positive, negative or mixed manner. M&As in nations other than India have received more academic attention  with respect to the effect on qualitative issues like cultural compatibility, downsizing and innovation. Cultural incompatibility and downsizing are problems of M&As in India as well as other nations. Indian domestic M&As have resulted in greater market share whereas majority of the M&As in other nations have lost customer base. Although literature studying the outcomes of M&As on firm performance from a pre-post perspective are multifarious, a comparative assessment of the studies on M&As occurring in India with those carried out in other nations of the world is a novel attempt.
Keywords: Market Growth; Innovation; Cultural Compatibility; Downsizing; Shareholders’ Wealth; Profitability; Mergers and acquisitions